HUBUNGAN ANTARA PERSEPSI PASIEN TENTANG KUALITAS DAN KEMAUAN MEMBAYAR PELAYANAN KESEHATAN GIGI DI MMC UMS - Karyadi, Edi (Universitas Muhamadiyah Surakarta, 2011)
Until now there is no standard for measuring the standard willingnesss to pay of patients and patient satisfaction for the quality of dental care. Research purposes to assess the magnitude of willingness to pay for outpatient dental care and want to test the factors that affect willingness to pay for outpatient dental care at the Muhammadiyah Medical Center (MMC UMS). This study was observational analytic study with cross-sectional approach, where all the variables studied were observed at the same time. The study population was patients who received outpatient dental care with simple random sampling. To the adequacy of the sample required a minimum sample size of 120. The data collection by questionnaire content validity technique. The results showed 60.8% of patient education level is college. The average patient?s willingness to pay for dental care Rp.60.833. The average satisfaction score of patients on dental health servicesis 77.35 (including the high satisfaction category). While the average patient income for Rp.2.110.417. Statistical analysis proves? there is a positive correlation? between service quality and willingness to pay for dental care patients (r=0247, p <0.05). In this study also proves? there is a positive correlation? between the patient and the willingness to pay in comedental care (r=0.730, p <0.05). With the regression test showed the ?threev ariables (education, income and quality of service)? jointly able to predict variations in the willingness of patients to pay for 59.7% and statistically ? t regression model (valid) (p <0.001).Keywords: education, income, quality of service, willingnestopay